2015 IEEE International Symposium on Electromagnetic Compatibility (EMC) 2015
DOI: 10.1109/isemc.2015.7256135
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radio signal propagation through window panes and energy saving windows

Abstract: Abstract-Glass windows have undergone an energy saving evolution over the past three, four decades, from single panes till today's ultralow-emission windows. While the earliest energy saving windows were constructed as a sandwich of clear glass panes using the vacuum-flask principle, modern low-emission windows includes panes with coatings of metal and/or metal oxides. This coating has caused radio propagation problems for communication systems; something that may be utilized to protect a building from intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…A maximum attenuation of around 50 dB is observed for window1 (V-V polarization) and window3 (H-H polarization). At frequencies falling within the studied band in this latter, maximum attenuation has been found for modern windows of: 60 dB in [4]; 38 dB in [5]; 22 dB in [6]; and 36 dB in [7]. These results also indicate the high losses which the contemporary windows introduce.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…A maximum attenuation of around 50 dB is observed for window1 (V-V polarization) and window3 (H-H polarization). At frequencies falling within the studied band in this latter, maximum attenuation has been found for modern windows of: 60 dB in [4]; 38 dB in [5]; 22 dB in [6]; and 36 dB in [7]. These results also indicate the high losses which the contemporary windows introduce.…”
Section: Resultsmentioning
confidence: 61%
“…However, new windows have sophisticated frames with several thick glass panes. This construction together with metal coating of the glasses aims to achieve good thermal isolation (high energyefficiency) by reflecting the infrared radiation and to prevent the ultraviolet part of the spectrum to enter the building [4], [5]. At present, information about the loss introduced by these advanced windows is even more important than before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate the dependence of SE on the gap between the glass panes, measurements of Low-E windows were performed in an anechoic chamber. There are several other methods for measuring SE which include either close proximity experiments [7,10] or measurements in a reverberation chamber [7,19]. The former method has a high measurement error because multiple reflections occur between antennas standing tenths of centimetres from each other.…”
Section: Measurement Setup and Sample Designmentioning
confidence: 99%
“…An in-depth theoretical analysis on single, double and laminated shields was made by Schulz et al in 1988 [6]. It was found that these coatings can attenuate microwaves up to 50 dB in a range of 1 to 12 GHz frequency [7][8][9]. This means that mobile communication frequencies, GPS and WiFi, can be highly attenuated by Low-E windows [2,10,11].…”
Section: Introductionmentioning
confidence: 99%